Enhanced ammonia nitrogen removal from actual rare earth element tailings (REEs) wastewater by microalgae-bacteria symbiosis system (MBS): Ratio optimization of microalgae to bacteria and mechanism analysis. (January 2023) - Liu, Zhuochao; Cui, Dan; Liu, Yuanqi; Wang, Haiyu; Yang, Liming; Chen, Houxing; Qiu, Genping; Xiong, Zhensheng; Shao, Penghui; Luo, Xubiao
Graphical abstract: Highlights: The rare earth wastewater was firstly treated using a microalgae-bacteria system. The microalgae-bacteria ratio showed positively correlated with NH4 + -N removal. High NH4 + -N removal of 97.46 % was achieved at microalgae/bacteria ratio of 1:3. Bacteria altered the microbial diversity and promoted functional microalgae growth. Abstract: Microalgae-bacteria symbiosis system (MBS) appear to be a promising way for treating the rare earth elements (REEs) wastewater due to the natural symbiotic interactions between microalgae and bacteria. Herein, we investigated the effect of different inoculation ratios of microalgae and bacteria including 3:1 (MB_1), 1:1 (MB_2) and 1:3 (MB_3) on NH4 + -N removal from REEs wastewater and analyzed the corresponding biological mechanism. The NH4 + -N removal rate with MB_3 reached 17.69 ± 0.45 mg NH4 + -N/L d −1, which was 2.58 times higher than that in single microalgae system. The results were further verified in continuous feeding photobioreactors and kept stable for 100 days. Metagenomic analysis revealed that the abundance of genes related to microalgae assimilation increased by 14 %-50 % in answer to photosynthesis and NH4 + -N absorption, while that related to nitrification apparently dropped, indicating that MBS was a sustainable method capable of enhancing NH4 + -N removal from REEs wastewater.